Classroom for adults, vocational training and mothers in the canteen (Journal of Parents and Teachers, 2026)
Schools in San José de Valencia carry out social work that reaches out to various groups through their adult education classes, specialist vocational training for young people, support for those with special educational needs, and the school canteen volunteering scheme, where mothers volunteer their time, thereby helping to reduce costs for families.
Keywords: Community work; Community groups; Special needs